Rat Animal Model of Pectus Excavatum - David, Vlad-Laurentiu; Ciornei, Bogdan; Horhat, Florin-George; Amaricai, Elena; Horhat, Ioana-Delia; Hoinoiu, Teodora; Boia, Eugen-Sorin (Life (Basel, Switzerland), 2020)
Background: pectus excavatum (PE) is the most common congenital deformity of the thoracic wall. Lately, significant achievements have been made in finding new, less invasive treatment methods for PE. However, most of the experimental work was carried out without the help of an animal model. In this report we describe a method to create an animal model for PE in Sprague-Dawley rats. Methods: We selected 15 Sprague-Dawley rat pups and divided them into two groups: 10 for the experimental group (EG) and 5 for the control group (CG). We surgically resected the last four pairs of costal cartilages in rats from the EG. The animals were assessed by CT-scan prior to surgery and weekly for four consecutive weeks. After four weeks, the animals were euthanized and the thoracic cage was dissected from the surrounding tissue. Results: On the first postoperative CT, seven days after surgery, we observed a marked depression of the lower sternum in all animals from the EG. This deformity was present at every CT-scan after surgery and at the post-euthanasia assessment. Conclusions: By decreasing the structural strength of the lower costal cartilages, we produced a PE animal model in Sprague-Dawley rats.